Classifying Musical Medium of Performance: Object or Property? - Griscom, Richard; Henry, Joshua; Lee, Deborah; Smiraglia, Richard P; Szostak, Rick; Young, J. Bradford (Notes (Music Library Association), 2024)
How best to classify musical medium of performance? We welcome the advice and expertise of the community of Notes readers to inform our deliberations. Specifically, when referring to the sources of musical sound, should we be describing the objects (e.g., aerophone), the properties (e.g., piccolo), or some combination of the two? The Institute for Knowledge Organization and Structure convened a research group to discuss “the phenomena of music for classification.” What does it mean to classify the phenomena of music rather than musical documents or documents containing texts about music? How might we represent music apart from its documentary representations (scores, recordings, etc.)? We considered the Library of Congress Medium of Performance Thesaurus (LCMPT) and Hornbostel-Sachs (H-S) classification. The universal Basic Concepts Classification (BCC) is interdisciplinary and is organized around phenomena (things), relators (the relationships that exist among phenomena), and the properties that phenomena and relators may possess. We sought a comprehensive classification of medium of performance for the BCC. H-S focuses on the physical nature of instruments and how they make sound, the LCMPT effectively identifies specific instruments by name. H-S does not provide the level of granularity that we need but LCMPT’s larger set of terms are organized with only a few layers of hierarchy. H-S avoids local nomenclature, LCMPT embraces it. The two are attractive because they provide well-developed vocabulary and because their differences manifest as different strengths for a Semantic Web application. Ultimately our analysis reaches no specific conclusion. Instead, we have reflected thoroughly on the panoply of phenomena associated with the representation of medium of performance as phenomena of music in nondocumentary contexts.